CONSTITUTIONALISM AND PUBLIC HEALTH EMERGENCIES: COVID-19 REGULATIONS IN SOUTH AFRICA AND THE CONSTITUTIONAL AND HUMAN RIGHTS SLIPPERY SLOPE - Annie Singh; Simbarashe Tembo (Obiter, 2022)
This article provides a theoretical and factual-legal analysis of South Africa’s response to the COVID-19. The state of disaster and its related COVID-19 regulations are interrogated from a constitutional and human rights perspective. It is conceded that public health emergencies call for a limitation of certain rights to control or curb the spread of the pandemic. However, the measures adopted by the South African government were in some respects disproportional and violated the constitutional and human rights principles. This article carefully examines the South African approach in instances where the constitutional and human rights of its people were brought into contention. For purposes of clarity, the focus is on documented accounts of the violations of fundamental human rights during the declaration and the operation of Lockdown Regulations in terms of the Disaster Management Act 2002.